Validation of Earth atmosphere models using solar EUV observations from the CORONAS and PROBA2 satellites in occultation mode - Slemzin Vladimir; Ulyanov Artyom; Gaikovich Konstantin; Kuzin Sergey; Pertsov Andrey; Berghmans David; Dominique Marie (Journal of Space Weather and Space Climate, 2016)
Aims: Knowledge of properties of the Earth’s upper atmosphere is important for predicting the lifetime of low-orbit spacecraft as well as for planning operation of space instruments whose data may be distorted by atmospheric effects. The accuracy of the models commonly used for simulating the structure of the atmosphere is limited by the scarcity of the observations they are based on, so improvement of these models requires validation under different atmospheric conditions. Measurements of the absorption of the solar extreme ultraviolet (EUV) radiation in the upper atmosphere below 500 km by instruments operating on low-Earth orbits (LEO) satellites provide efficient means for such validation as well as for continuous monitoring of the upper atmosphere and for studying its response to the solar and geomagnetic activity.